Pembelajaran Tell Me What You See (Lihat Ucap) dalam Meningkatkan Kemampuan Menceritakan Tokoh Idola pada Siswa Kelas VII SMPN 1 Kediri Tahun Pelajaran 2022 - Haeri, Zul; Yunus, Muhamad (YASIN, 2022)
Learning to tell me what you see (see word) aims to provide opportunities for students to develop existing abilities by giving freedom of imagination in telling about idol figures. Based on the results of the documentation obtained information that from 26 students of class VII such as class VII C the average score obtained is only 7.03, while the maximum classical completeness score (KKM) determined by the teacher is 7.0. The data collection instruments in this study were test, documentation, and observation techniques. The data analysis used in this research is descriptive quantitative. From the results of data analysis, it can be concluded that individually in the learning process telling about idol figures has not been satisfactory, the highest score is 80 and the lowest score is 56. If categorized, 17 students with high ability or 61.54%, moderate ability will be obtained. as many as 9 people or 38.46% and those with low abilities did not exist or 0%. In the group (GPA) including Normal with a value of 68.31. In the first cycle, it was quite satisfactory, namely the highest score was 80 and the lowest score was 64. If categorized, it would be obtained students who have high abilities as many as 24 people or 92.31%, moderate abilities 2 people or 7.69% and those with low abilities do not exist or 0 %. In the group (GPA) Normal with a value of 73.23. While in the second cycle it is very satisfying, namely the highest score is 84 and the lowest score is 64. If categorized, it will be obtained students who have high ability as many as 25 people or 96.15%, moderate ability 1 person or 3.85% and low ability none or 0%. In the group (GPA) High with a value of 76.31.